The Analysis of Target Drone Wing Sweep Angle on Dynamic Stall Condition with Pitch Rate Variation using Computational Fluid Dynamics - Bramantya, Muhammad Agung; Nugroho, Gesang (Diponegoro University, 2025)
A target drone is a type of Unmanned Aerial Vehicle (UAV) with a special mission as a shooting target in the military field. Target drones must be able to fly at high speeds and be agile. This study discusses the influence of the wing sweep angle on the aerodynamic performance of a target drone during dynamic stall conditions. Banshee Whirlwind-like model is used as a research object in this study with the adjustment of the empennage design to a V-Tail configuration. Furthermore, the wing sweep angle was varied to determine its effect on dynamic stall conditions using Computational Fluid Dynamics (CFD) in transient conditions. The wing sweep angle variations used were 5°, 20°, 35°, and 50°, whereas the dynamic stall condition was varied using pitch rates of 3.6°/s, 6°/s, and 18°/s. The aerodynamic performance discussed relates to the lift force, drag force, efficiency, stall angle, lateral stability, and stall development phase. The results of this study indicate that a wing sweep angle of 50° is the most optimal design in terms of stall condition, stability, and maneuverability.